2017
DOI: 10.1080/13645706.2017.1303516
|View full text |Cite
|
Sign up to set email alerts
|

Validation of psychomotor tasks by Simbionix LAP Mentor simulator and identifying the target group

Abstract: The trainer could be beneficial for medical students and surgical novices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For example, the MIST-VR system was developed to teach basic laparoscopic skills, suturing, and knot-tying [67] . High-fidelity VR systems include the Lap Mentor which incorporates over 65 cases in the fields of general surgery, gynecology, urology, and bariatric surgery [68,69] . The potential of VR for training and monitoring basic laparoscopic skills and full laparoscopic procedures is well recognized [70] .…”
Section: Ais In Surgical Education and Training For Womenmentioning
confidence: 99%
“…For example, the MIST-VR system was developed to teach basic laparoscopic skills, suturing, and knot-tying [67] . High-fidelity VR systems include the Lap Mentor which incorporates over 65 cases in the fields of general surgery, gynecology, urology, and bariatric surgery [68,69] . The potential of VR for training and monitoring basic laparoscopic skills and full laparoscopic procedures is well recognized [70] .…”
Section: Ais In Surgical Education and Training For Womenmentioning
confidence: 99%
“…Some studies have shown that persons who play video games in their personal lives are able to handle virtual reality trainers more competently [ 13 , 14 , 15 , 16 ]. Medina and Barraza found that professional musicians are able to control their attention more effectively than nonmusicians [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the increasingly limited human and financial resources, as well as higher ethical standards in modern medicine, surgical education must necessarily encompass new training concepts [ 3 , 4 ]. Rapid advancements in medical and digital technology, especially minimally invasive surgery, have resulted in a wide range of training and educational opportunities, such as virtual reality training devices or interactive video learning platforms [ 5 , 6 , 7 , 8 ]. In view of these new options, the traditional concept of acquiring knowledge of surgical anatomy on vulnerable patients entrusted to our care appears to be debatable, at least from the ethical point of view [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%